Trade-off between wire matrix and twisted tape: SOLTRACE® based indoor study of parabolic trough collector. (August 2020) - Varun, K.; Arunachala, U.C.; Elton, D.N.
Abstract: Heat transfer augmentation using turbulators in PTC is well known. However, based on the methodology its thermo-hydraulic rating can vary. In the present experimental study, variations of wire matrix and twisted tape have been used to analyse the thermo-hydraulic behavior of the PTC by referring two approaches viz. thermo-hydraulic efficiency and performance evaluation criterion. An innovative method comprising, analytical model-SOLTRACE®- differential resistance heating is incorporated to simulate the highly non-uniform solar irradiance over the receiver in an indoor test rig. Under the same operating condition, thermo-hydraulic efficiency of medium dense wire matrix is maximum whereas twisted tape of twist ratio 3.37 yields better result as per performance evaluation criterion. However, thermo-hydraulic efficiency based analysis is recommended due to the role of realistic pumping power. Further, variation in energy parameters viz. thermal efficiency, pumping power, Nusselt number and their effect on receiver length have been analyzed. The trade-off between two inserts is also discussed with respect to operating condition. Graphical abstract: Image 1 Highlights: The realistic non-uniform solar flux is simulated in the indoor setup. Variation in PTC performance rating by referring two thermo-hydraulic approaches have been discussed. Effect of thermal performance enhancement on the receiver length is analyzed.